The effects of three varied cycle leg protocols on selfpaced run time trial performance - Davoren, B.; Gregory, J. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
In the past, the cycling portion of an Olympic Distance Triathlon (ODT) was typically performed at steady state power outputs. However, with the advent of drafting and the inclusion of smaller spectator friendly bike courses, the demands of the cycle leg have changed. The purpose of this research was to investigate the effect of three varied cycle leg protocols on self-paced run time trial performance. Subjects (n=4) completed an initial phase of testing to determine baseline information. A 7.5 km run time trial on the treadmill (RTT) was followed by progressive maximal run (RT) and cycle tests (CT) 72 hours later. The best run performance was established using the RTT, whilst the individual anaerobic threshold (IAT), maximal power and VO2max was recorded from the maximal tests. The subjects then completed three cycle leg protocols each of 45 minutes in duration, followed immediately by another 7.5km run time trial, with a minimum of 72 hours recovery between testing protocols. This bike-run combination is referred to as a BRICK. The three protocols were conducted in a randomised counter-balanced manner and included: a simulated draft time trial (BRICKDRT), a self paced steady state time trial (BRICKITT) and a variable power output time trial (BRICKITU). Compared to the control RTT, the results demonstrated for all BRICK running protocols significantly lower (p<0.005) mid and end oxygen consumption (VO2) values, BRICKITT (3.61 ± .15, 3.73 ± .24), BRICKDRT (3.67 ± .24, 3.70 ± .24) and BRICK ITU (3.54 ± .22, 3.66 ± .15) v`s RT (3.90 ± .39, 3.95 ± .28). No significant differences were recorded between the RTT and the BRICK protocols for the measures of heart rate (HR), bicarbonate ion concentration (HCO3), lactate (HLa), pH, perceived exertion (RPE) and 7.5km run times. This research demonstrated a decrease in VO2 during the run leg of all BRICK protocols and indicated limitations in run pacing and velocity of competitive triathletes.